Interannual variability of the onset of the South China Sea summer monsoon - Luo, M.; Leung, Yee-Hong; Graf, H.; Herzog, M.; Zhang, W. (John Wiley & Sons Ltd., 2016)
© 2016 Royal Meteorological Society. This article investigates the year-to-year variability of the onset of the South China Sea summer monsoon (SCSSM) and the possible influences exerted by the surface temperature anomalies over land and sea. Early and late monsoon onsets are related to the temperature anomalies in different regions. It is found that an early onset follows negative sea surface temperature (SST) anomalies in the central tropical Pacific (CP) Ocean during the preceding winter and spring, corresponding to a CP La Niña. In contrast, a late onset is preceded by the negative surface air temperature anomalies over land in the central Asian continent. Negative SST anomalies in the central-eastern equatorial Pacific Ocean and the associated warming in the western Pacific induce an anomalously enhanced Walker circulation. This anomalous Walker cell leads to an increase in convection, causing more latent heat release and a subsequent decrease of surface pressure. The anomalous Walker cell and the enhanced latent heat release weaken the Western North Pacific subtropical high and the Philippine Sea anticyclone, favouring a westerly flow from the Indian Ocean, resulting in an early SCSSM onset. On the other hand, negative land surface temperature anomalies cool the atmosphere over land, and locally modify the Hadley circulation, accompanied by the anomalous divergence in the low-level atmosphere over the western equatorial Pacific. This divergence anomaly reduces the latent heat release and strengthens the anticyclone in the Philippine Sea, thus preventing the westward extension of the westerlies from the Indian Ocean and causing a late SCSSM onset.